PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENGANIAYAAN TERHADAP ANAK KANDUNG YANG MENGAKIBATKAN MENINGGAL DUNIA(Studi Putusan Nomor 109/Pid.Sus/2023/PN Kot) - Alika Kristinawati; I Ketut Seregig, Yulia Hesti (INTELIGENSIA MEDIA, 2024)
The KBBI defines violence as the actions of a person or group of people that cause physical damage to someone else's property or belongings. Violence is a physical or psychological act committed by a person or group of people intentionally or unintentionally, directly or indirectly, personally or structurally, and often parents commit acts of violence against children with the result that many children experience trauma or could even die. Torture is a violent crime committed on the human body in various forms, resulting in injury or pain to a person's body and even death. In the Criminal Code, the general understanding is that abuse is a criminal act against the human body. This writing is aimed at finding out criminal liability and the factors that cause perpetrators to abuse their biological children which results in their death. The method used in this research is normative legal research and empirical law, namely research whose sources come from books, legislation, journals, interviews and other sources.